INTEGRASI AI DALAM PEMBELAJARAN: DAMPAKNYA TERHADAP KEMANDIRIAN BELAJAR MAHASISWA - Rahmadi U; Muhammad Sahrir Aras (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study is simply analyzing the influence of AI use on student learning independence. This study employs systematic review which is using source that relevant to the topic of AI use in learning and the concept of self-directed learning. Data were analyzed descriptively by identifying key themes in terms of the use of AI in supporting the independent learning process. The results show that AI has great potential to improve student learning independence by providing instant feedback, and supporting personalized learning. However, uncontrolled use of AI can create dependency, reduce critical thinking skills, and reduce students' independent exploration efforts. Therefore, AI in learning should be balanced with pedagogical strategies that encourage reflection, critical thinking, and student responsibility for learning.